2020
DOI: 10.1080/17461391.2020.1730447
|View full text |Cite
|
Sign up to set email alerts
|

High rates of fat oxidation are maintained after the sleep low approach despite delayed carbohydrate feeding during exercise

Abstract: Training with low carbohydrate availability enhances endurance training adaptations but training volume may be compromised. We explored whole body metabolism and performance with delayed carbohydrate feeding during exercise undertaken following acute sleep low training. We hypothesised this strategy would not suppress fat oxidation and would maintain exercise performance. The study involved 3 experimental trials and included 9 men and 1 woman (V O 2 peak=58.8±5.5 mL • kg -1 • min -1 ). Each trial started in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The highest average 30 s of V̇O 2 was considered to be V˙O 2peak . W max was calculated as the power output from the final stage completed, combined with the fraction of the time spent in the following stage, multiplied by 30 W, as previously described ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…The highest average 30 s of V̇O 2 was considered to be V˙O 2peak . W max was calculated as the power output from the final stage completed, combined with the fraction of the time spent in the following stage, multiplied by 30 W, as previously described ( 17 ).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence from our laboratory has shown that the provision of a CHO-free sweet placebo drink could partially restore exercise capacity during a “sleep low-train low” approach [ 89 ]. Progressing this further, providing exogenous CHO ingestion during exercise under low CHO conditions does not impair fat oxidation during exercise [ 90 , 91 ] and therefore, providing a moderate dose of CHO may serve to improve exercise capacity by preventing hypoglycaemia during exercise and recovery. However, in our study, since HR data during LIT sessions were similar between SL and CON, we can hypothesise the intensity was sufficiently difficult for SL despite a reduction in power output.…”
Section: Discussionmentioning
confidence: 99%
“…Whether training adaptation can be enhanced with this approach has not been studied. More recently, building on previous work [157], the effects of delayed carbohydrate feeding in a glycogen depleted state (i.e., liver and muscle) on whole body metabolism and performance have been investigated [158]. While performance outcomes were unclear, delayed carbohydrate feeding enabled maintenance of stable blood glucose concentrations without suppressing fat oxidation rates and thus created a favorable metabolic response.…”
Section: Carbohydrate Periodizationmentioning
confidence: 99%